2011
DOI: 10.1103/physreve.84.026116
|View full text |Cite
|
Sign up to set email alerts
|

Efficient routing strategies in scale-free networks with limited bandwidth

Abstract: We study the traffic dynamics in complex networks where each link is assigned a limited and identical bandwidth. Although the first-in-first-out (FIFO) queuing rule is widely applied in the routing protocol of information packets, here we argue that if we drop this rule, the overall throughput of the network can be remarkably enhanced. We proposed some efficient routing strategies that do not strictly obey the FIFO rule. Comparing with the routine shortest path strategy, the throughput for both Barabási-Albert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…However, many factors, such as loading balancing and fault tolerance, may lead to some compromised strategies in which data packets are not always delivered through the shortest path in the real commercial transport network [78,79]. It has also been shown that the selection of the shortest paths between all pairs of nodes may lead to traffic congestion problem [80].…”
Section: Betweenness Centralitymentioning
confidence: 99%
“…However, many factors, such as loading balancing and fault tolerance, may lead to some compromised strategies in which data packets are not always delivered through the shortest path in the real commercial transport network [78,79]. It has also been shown that the selection of the shortest paths between all pairs of nodes may lead to traffic congestion problem [80].…”
Section: Betweenness Centralitymentioning
confidence: 99%
“…Thus, a measure w ij = (k i k j ) θ [33] was introduced as the weight of an edge. This measure has been adopted in many works for distinguishing the importance among edges in unweighted networks [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Many local routing strategies are based on the random-walk process [15]. Hybrid routing strategies [16][17][18][19][20][21][22] have been based on both global information (the shortest paths from one node to all the others), and local information (the degrees or local traffic loads of the neighboring nodes) in order to enhance network performance. However, our main focus in this paper is not so much on verifying the effectiveness of a certain routing strategy; rather we concentrate on the impact of different network structures on network performance.…”
Section: Introductionmentioning
confidence: 99%